Analisi Strategic Location dan Marketing Communication Terhadap Minat Beli di Perumahan Azalea Garden Tanggerang - Muhamad Al Faruq Abdullah; Fathihani Fathihani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study aims to determine the effect of strategic location and marketing communication on the purchasing decisions of respondents who are housing owners in Azalea Garden. This research is descriptive. Primary data and secondary data were obtained. Secondary data was obtained from various sources such as journals, books and other related primary publication data obtained by distributing questionnaires to target respondents. By using convenience sampling technique, the target sample is at least 100 respondents. The analytical method used in this research is Variance Based Structural Equation Modeling - Partial Least Square and data processing using SmartPLS version 3.0 program. This study shows the results that strategic location and marketing communication have a positive relationship and have a significant effect on purchase intention. The variability of strategic location and marketing communication constructs is 70.1% on purchase intention.